Reducing the physical ergonomic risk by job rotation: a simulation-based approach. Issue 1 (2021) - Rinaldi, M.; Caterino, M.; Fera, M.; Macchiaroli, R.
Abstract: Since years, researchers have proposed job rotation as a solution to balance physical workload and reduce ergonomic risk among operators. Simulation is a strong tool for rapid ergonomic analysis, which allows testing different configurations and evaluating the characteristics of different operators. Thanks to such tool, this study proposes a new approach to improve a real system and reduce the ergonomic risk among operators. A real assembly station has been involved in the study and a postural analysis has been performed considering real variables of the system. Different potential workers with different anthropometric characteristics have been tested. The critical situations have been identified and solved proposing different job rotation solutions. Simulation results confirm that job rotation is a good approach to reduce the ergonomic risk and they provide practical guidelines for task assignment.